DOI: 10.14264/uql.2014.248
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Consequences of Land use Changes for Bioenergy Crop Production at a Regional Scale

Abstract: Sustainability has become a focus of global bioenergy (especially biofuel) policy and research over the past few years. Due to the rapid expansion of demand for global bioenergy and increased sustainability requirements, land use change associated with bioenergy crops (hereafter referred to as 'bioenergy-driven land use change') has emerged as an important research topic. The use of degraded land, marginal and abandoned agricultural lands (hereafter referred to as 'underutilised agricultural land') has been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
(192 reference statements)
0
1
0
Order By: Relevance
“…Secondly, expansion of beef cattle grazing (5.2% between 1992/93 and 2005/ 06) has been a notable land use change in the case study catchment over the past few decades. Interviews with local agronomists confirmed that 'unproductive' or 'marginal' cropping lands previously used for dryland agriculture have been converted to beef cattle grazing due mainly to declining profitability of dryland agriculture (Miyake, 2013). Conversion of some land used for beef cattle grazing to bioenergy cropping might bring additional economic opportunities for the region.…”
Section: Land Use Change Pathways Suited To the Subtropical Australiamentioning
confidence: 99%
“…Secondly, expansion of beef cattle grazing (5.2% between 1992/93 and 2005/ 06) has been a notable land use change in the case study catchment over the past few decades. Interviews with local agronomists confirmed that 'unproductive' or 'marginal' cropping lands previously used for dryland agriculture have been converted to beef cattle grazing due mainly to declining profitability of dryland agriculture (Miyake, 2013). Conversion of some land used for beef cattle grazing to bioenergy cropping might bring additional economic opportunities for the region.…”
Section: Land Use Change Pathways Suited To the Subtropical Australiamentioning
confidence: 99%